Fine‐Tuning 2D Heterogeneous Channels for Charge‐Lock Enhanced Lithium Separation from Brine - Yaxin Hao; Xin Liu; Yaoling Zhang; Xin Zhang; Zhan Li; Ximeng Chen (Advanced Science)
Abstract The extraction of lithium (Li) from complex brines presents significant challenges due to the interference of competing ions, particularly magnesium (Mg2⁺), which complicates the selective separation process. Herein, a strategy is introduced employing charge‐lock enhanced 2D heterogeneous channels for the rapid and selective uptake of Li⁺. This approach integrates porous ZnFe2O4/ZnO nanosheets into Ag+‐modulated sub‐nanometer interlayer channels, forming channels optimized for Li⁺ extraction. The novelty lies in the charge‐lock mechanism, which selectively captures Mg2⁺ ions, thereby facilitating the effective separation of Li from Mg. This mechanism is driven by a charge transfer during the formation of ZnFe2O4/ZnO, rendering O atoms in Fe‐O bonds more negatively charged. These negative charges strongly interact with the high charge density of Mg2⁺ ions, enabling the charge‐locking mechanism and the targeted capture of Mg2⁺. Optimization with Ag⁺ further improves interlayer spacing, increasing ion transport rates and addressing the swelling issue typical of 2D membranes. The resultant membrane showcases high water flux (44.37 L m⁻2 h⁻¹ bar⁻¹) and an impressive 99.8% rejection of Mg2⁺ in real brine conditions, achieving a Li⁺/Mg2⁺ selectivity of 59.3, surpassing existing brine separation membranes. Additionally, this membrane demonstrates superior cyclic stability, highlighting its high potential for industrial applications.